Antioxidant indices and amino acid composition of phenolic containing Lima beans (Phaseolus lunatus) after simulated human gastrointestinal digestion - Sule O. Salawu; Oluwaseun M. Folorunso; Akintunde A. Akindahunsi; Aline A. Boligon (International Journal of Food Studies)
The present investigation was designed to characterize the phenolic profile of Lima beans (Phaseolus Lunatus) and also to evaluate the antioxidant indices: total phenolic content (TPC), total flavonoid content (TFC), ferric reducing antioxidant power (FRAP), 2,2-Diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity and amino acid composition at different stages of simulated gastrointestinal digestion (oral, gastric, intestinal). High Performance Liquid Chromatography (HPLC-DAD) analysis revealed the presence of some phenolic compounds (gallic acid, catechin, caffeic acid, rutin, quercitrin, quercetin, kaempferol and apigenin), with a reduced amount (mg/g) after cooking: gallic acid (raw: 1.96 ± 0.02; cooked: 1.82 ± 0.01); catechin (raw: 0.83 ± 0.01; cooked: 0.73 ± 0.01); rutin (raw: 2.61 ± 0.03; cooked:1.74 ± 0.03); quercitrin (raw: 5.73 ± 0.01; cooked: 5.68 ± 0.01); apigenin (raw: 2.09 ± 0.01; cooked: 1.79 ± 0.02), with exception of quercetin (raw: 2.11 ± 0.02; cooked: 5.73 ± 0.02) and caffeic acid (raw: 2.08±0.04; cooked 2.95 ± 0.04). The results of the antioxidant indices of in vitro enzyme digested lima beans revealed higher values for cooked Lima beans compared to the raw counterpart, with a stepwise increase at the different stages of in vitro digestion, with the exception of ferric reducing antioxidant power; TPC (oral digestion: 65.44 ± 0.96; gastric digestion:134.87 ± 0.46; intestinal digestion: 517.72 ± 4.70; mg/g tannic acid equivalent), TFC (oral digestion: 199.30 ± 6.43; gastric digestion: 1065.97± 1.22; intestinal digestion: 3691.87 ± 4.2; mg/g quercetin equivalent), DPPH (oral digestion: 85800.00 ± 305.50; gastric digestion: 99066.66 ± 115.47; intestinal digestion: 211354.20 ± 360.84; µmol TE/g sample). The results also revealed a progressive increase in the antioxidant indices and amino acid composition (mg/kg) for both raw and processed lima beans at various stages of the in vitro digestion, with the intestinal phase of simulated digestion ranking higher. This implied that the Lima beans contained some essential amino acids and antioxidant molecules that would be readily available after passing through the gastrointestinal tract and could therefore be explored as functional food in the management of free radical mediated diseases.